Sintering Temperature Induced Evolution of Microstructures and Enhanced Electrochemical Performances: Sol-Gel Derived LiFe(MoO4)2 Microcrystals as a Promising Anode Material for Lithium-Ion Batteries - Wang, Li; He, Yuanchuan; Mu, Yanlin; Liu, Mengjiao; Chen, Yuanfu; Zhao, Yan; Lai, Xin; Bi, Jian; Gao, Daojiang (Frontiers in Chemistry, 2018)
A facile sol-gel process was used for synthesis of LiFe(MoO4)2 microcrystals. The effects of sintering temperature on the microstructures and electrochemical performances of the as-synthesized samples were systematically investigated through XRD, SEM and electrochemical performance characterization. When sintered at 650 ℃, the obtained LiFe(MoO4)2 microcrystals show regular shape and uniform size distribution with mean size of 1-2 μm. At the lower temperature (600 ℃), the obtained LiFe(MoO4)2 microcrystals possess relative inferior crystallinity, irregular morphology and vague grain boundary. At the higher temperatures (680 and 700 ℃), the obtained LiFe(MoO4)2 microcrystals are larger and thicker particles. The electrochemical results demonstrate that the optimized LiFe(MoO4)2 microcrystals (650 ℃) can deliver a high discharge specific capacity of 925 mAh g-1 even at a current rate of 1 C (1050 mA g-1) after 500 cycles. Our work can provide a good guidance for the controllable synthesis of other transition metal NASICON-type electrode materials.